1999
DOI: 10.1007/s004249900079
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine-kinase-dependent regulation of the nitric oxide synthase gene by endothelin-1 in human endothelial cells

Abstract: In vascular endothelium, endothelium-derived relaxing factor, predominantly nitric oxide (NO), is synthesized by endothelial NO synthase (eNOS). While regulatory influences on eNOS enzyme activity are widely clarified, little is known about the regulation of the eNOS gene. We investigated the regulatory signaling mechanisms of eNOS mRNA expression and accumulated NO production in human endothelial cells. Northern blot analysis and NO assays demonstrate that the vasoconstrictor peptide endothelin-1 (ET-1) induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…However, there is evidence suggesting that activation of ET A receptors also stimulates NO release. Marsen et al . (1999) showed that ET‐1 acting on ET A receptors induces eNOS gene expression via tyrosine kinase‐ and protein kinase‐dependent pathways.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence suggesting that activation of ET A receptors also stimulates NO release. Marsen et al . (1999) showed that ET‐1 acting on ET A receptors induces eNOS gene expression via tyrosine kinase‐ and protein kinase‐dependent pathways.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been shown that adenosine, via the A 2a receptor, induces NO production in HUVECs and that this is mediated via the MEK1/2/ERK1/2 pathway [48]. There is also evidence that, in HUVECs, endothelin-induced NOS 3 regulation is tyrosine kinase-dependent [49], which is of relevance since ERK1/2 is a tyrosine kinase; furthermore, bAR-mediated PKA signalling can activate MAPK through switching of the coupling of bARs from a G s protein to a G i protein as a consequence of PKA-mediated b 2 AR phosphorylation [50]. PKA itself has also been shown to activate the MAPK cascade through direct stimulation of Rap 1 [51].…”
Section: The Mek/erk Pathwaymentioning
confidence: 96%
“…However, it was reported that ethanol induced a rapid increase of ecNOS protein and mRNA expression levels and activity [44][45][46][47][48]. Ethanol modulates tyrosine kinase activity [49], and tyrosine kinase regulates expression of ecNOS via posttranscriptional mechanisms [50,51]. In addition, ethanol dose dependently increased basal ecNOS activity via a mechanism involving a pertussis toxin-sensitive G protein in the absence of any effect on cell viability or NOS protein expression [46].…”
Section: Discussionmentioning
confidence: 99%